2017
DOI: 10.1186/s13020-016-0123-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical profiles and effectiveness between Erxian decoction and mixtures of decoctions of its individual herbs: a novel approach for identification of the standard chemicals

Abstract: BackgroundIdentification of bioactive standard chemicals is a major challenge in the study of the Chinese medicinal formula. In particular, the chemical components may interact differently depending on the preparative methods, therefore affecting the amounts of bioactive components and their pharmacological properties in the medicinal formula. With the use of Erxian decoction (EXD) as a study model—a  well-known Chinese medicinal formula for treating menopausal symptoms, a novel and rapid approach in seeking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The petiole juice has a sharp acidic flavor. The oxalic acid in the petioles is much lower, the proportion of oxalic acid is about 10% of the total 2–2.5% acidity, which is dominated by nontoxic malic acid [ 7 ]. This means that the stalks are not hazardous to eat but have a very tart taste [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The petiole juice has a sharp acidic flavor. The oxalic acid in the petioles is much lower, the proportion of oxalic acid is about 10% of the total 2–2.5% acidity, which is dominated by nontoxic malic acid [ 7 ]. This means that the stalks are not hazardous to eat but have a very tart taste [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of rhubarb includes anthraquinones, anthrones, stilbenes, tannins, polysaccharides, etc., which show extensive pharmacological activities including gastrointestinal regulation, anticancer and antimicrobial properties, hepatoprotection, cardiovascular and cerebrovascular anti-inflammatory protection, etc. [ 7 , 8 ]. The main characteristics of rhubarb quality are taste and aroma, which depend on the chemical composition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The soil pH and fertility have been shown to be strongly linked with soil microbial communities ( Shen et al, 2013 ; Siciliano et al, 2014 ). In the rhizosphere of ginseng plants, the soil pH and nutrient concentrations decline with increasing years of cultivation, ultimately leading to decreased microbial diversity, which in turn is responsible for the development of soil-borne ginseng diseases ( Nguyen et al, 2016a ; Xiao et al, 2016a ; Dong et al, 2017 ). It has also been demonstrated that allelochemicals (root exudates) of P. ginseng significantly decrease the genetic diversity and carbon-metabolic activity of microorganisms and cause chemotaxis responses of ginseng pathogenic microorganisms ( Li et al, 2014c , 2016 ; Lei et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PI3K/AKT/mTOR is a widely studied signaling pathway that mediates the phenotype and injury of podocytes in DN. Stimulated by AGEs, PI3K/AKT can also promote NF-κB and aggravate inflammation ( Ahmad et al, 2013 ; Hong et al, 2017 ). Recently, C-reactive protein (CRP) has been found to trigger a novel NF-κB-involved signaling pathway in the progression of DN, more narrowly, in human CRP transfected-db/db mice and cultured renal tubular epithelial cells, CRP is proved to promote inflammation via the evoking and dimerization of dipeptidyl peptidase-4 (DPP4) through DPP4/CD32b/NF-kB signaling circuit.…”
Section: Inflammation In the Progression Of Dnmentioning
confidence: 99%